Chinese Trust in the Police: The Impact of Political Efficacy and Participation. (22nd July 2015) - Hu, Rong; Sun, Ivan Y.; Wu, Yuning
Abstract : Objective: We assessed the influences of political efficacy and political participation on public perceptions of police trustworthiness in China. Methods: Drawing upon approximately 10, 000 cases collected by the Chinese General Social Survey (CGSS), we used multivariate regression to assess the impact of two types of political efficacy, internal efficacy and external efficacy, and three forms of political participation, engaging in community affairs, grassroots election, and rightful resistance, on public trust in the police, controlling for demographics and social trust and justice. Results: We found that external efficacy and grassroots election are positively related to trust in the police, whereas internal efficacy and rightful resistance are negatively associated with such trust. Background characteristics, such as gender, ethnicity, age, education, and household registration, and social trust and justice variables are also predictive of Chinese perceptions of police trustworthiness. Conclusion: Political efficacy and participation mattered in influencing trust in the police. The Chinese government should continue its political reforms by allowing greater public participation in the selection of political representatives and the decision‐making process of public policy.